Direct synthesis of noble metal nanostructures on carbon support by hydrothermal process - Sanja Krstić; Vladislava M. Jovanović (Zaštita Materijala)
Nanostructures of noble metals (Pt and Ag) on carbon support were prepared from fructose and solution of the Nobel metal salts (H2PtCl6 x 6H2O or AgNO3) under hydrothermal conditions. Commercial fructose (C6H12O6) acts as the carbon source and reducing agent and noble metal salts is a source of the metal to be incorporated in the new formed carbon material structure. The crystalline structure was examined by X-ray diffraction (XRD) and morphology investigated by scanning electron microscopy (SEM). The crystallite size of the deposited particles could be estimated by evaluating the line width of the Bragg peak applying the Scherrer method. All the XRD patterns clearly show the five main characteristic peaks of the face-centered cubic (fcc) crystalline for both Pt and Ag crystallite. The obtained Pt crystallite sizes were below 5.5 nm, while the Ag crystallite sizes were about 32 or 34nm.